Functional relationship between matrix metalloproteinase‐11 and matrix metalloproteinase‐14. (1st August 2014) - Buache, Emilie; Thai, Robert; Wendling, Corinne; Alpy, Fabien; Page, Adeline; Chenard, Marie‐Pierre; Dive, Vincent; Ruff, Marc; Dejaegere, Annick; Tomasetto, Catherine; Rio, Marie‐Christine
Abstract MMP‐11 is a key factor in physiopathological tissue remodeling. As an active form is secreted, its activity must be tightly regulated to avoid detrimental effects. Although TIMP‐1 and TIMP‐2 reversibly inhibit MMP‐11, another more drastic scenario, presumably via hydrolysis, could be hypothesized. In this context, we have investigated the possible implication of MMP‐14, since it exhibits a spatiotemporal localization similar to MMP‐11. Using native HFL1‐produced MMP‐11 and HT‐1080‐produced MMP‐14 as well as recombinant proteins, we show that MMP‐11 is a MMP‐14 substrate. MMP‐14 cleaves MMP‐11 catalytic domain at the PGG(P1)‐I(P1′)LA and V/IQH(P1)‐L(P1′)YG scissile bonds, two new cleavage sites. Interestingly, a functional test showed a dramatical reduction in MMP‐11 enzymatic activity when incubated with active MMP‐14, whereas inactive point‐mutated MMP‐14 had no effect. This function is conserved between human and mouse. Thus, in addition to the canonical reversible TIMP‐dependent inhibitory system, irreversible MMP proteolytic inactivation might occur by cleavage of the catalytic domain in a MMP‐dependent manner. Since MMP‐14 is produced by HT‐1080 cancer cells, whereas MMP‐11 is secreted by HFL1 stromal cells, our findings support the emerging importance of tumor‐stroma interaction/cross‐talk. Moreover, they highlight a Janus‐faced MMP‐14 function in the MMP cascade, favoring activation of several pro‐MMPs, but limiting MMP‐11 activity. Finally, both MMPs are active at the cell periphery. Since MMP‐14 is present at the cell membrane, whereas MMP‐11 is soluble into the cellular microenvironment, this MMP‐14 function might represent one critical regulatory mechanism to control the extent of pericellular MMP‐11 bioavailability and protect cells from excessive/inappropriate MMP‐11 function.